Some comments on the determination of fluvial sediment concentrations in the laboratory - Lai, Food See (Universiti Putra Malaysia Press, 1994)
The separation of suspended sediment in natural waters in the laboratories is usually determined by using the filtration method or gravimetric analysis. The type of filter used, however, differs from one user to another, the type being largely determined by the quality of data needed, cost or the effective filtering area required. In this experiment, four commonly used and recommended filters by various researchers and agencies in the country were tested. They are the Whatman 542, Whatman GFC, Whatman cellulose nitrate and Millipore type HA. The experiment involved drying the filters in the oven at 105°C for over 24 hand ashing in the muffle furnace at 5500C for 2h, a normal procedure in determining the mineral sediment weight by eliminating any organic matter present. After ashing, the Whatman GFC registered the highest mean weight loss of 0.0712g which is 3.63% ofthe original weight, followed by Whatman cellulose nitrate membrane and the Whatman 542 (0.0014g) and the Millipore Type HA (0.0004g).